Perancangan Meja Las yang Ergonomis berdasarkan Analysis REBA di Universitas Sebelas Maret - Komarudin Komarudin; Towip Towip (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
Welding practice is one type of practice with a fairly long duration. Therefore, an ergonomic welding table design is needed so that the practice can practice safely and comfortably. The purpose of this study was to evaluate existing designs with the REBA analysis approach and then redesign the more ergonomic welding table. Data collection technique using purposive sampling technique. The proposed welding table design is based on anthropometric data of 30 UNS Mechanical Engineering Education students class of 2018, 2019, and 2020. The design design of this welding table uses SolidWork 2019 software. The calculation of ergonomic risk evaluation with REBA resulted in a score of 6 meaning that immediate improvement is needed and requires further investigation. The results of this study obtained a new welding table design design that has dimensions: 42 cm in length, 40 cm in width, and 2,010 cm in height. This welding table also provides space to put the welding machine under the welding table. Thus, the improvement of the design of the welding table will increase the efficiency of the implementation of the practice. In addition, the practice will be safer and more comfortable because the welding table has adjusted to the posture of the average student.